Popularity and Representation of Zheng He’s Image: Pre-Eliminary Research - Rofiyarti, Fitri (Journal of Integrative International Relations, 2020)
Zheng He (Cheng ho) Mosques become iconic mosques in Indonesia as its architecture represents well Chinese culture. Even though, the legacy of the figure behind this name turned out to be a concern. Many people do not know that Zheng He is one of the figure who has contributed greatly to spread Islam in Indonesia. For this reason, the major objective of this study is investigating how Zheng He’s image and perception formed in the view of young Muslims, as the new generation who have big responsibilities related to the continuity and the development of Islam. The other purposes of this research is to find out how far Zheng He is known, as a diplomat and great explorer, become a role model in the process of young Muslim’s character building. Furthermore, reconstruction is carried out to form a positive image and perception of Zheng He and reconstruct the representation of Chinese culture and its relation to Islam.